From Grape By-Products to Enriched Yogurt Containing Pomace Extract Loaded in Nanotechnological Nutriosomes Tailored for Promoting Gastro-Intestinal Wellness - Ines Castangia; Federica Fulgheri; Francisco Javier Leyva-Jimenez; Maria Elena Alañón; Maria de la Luz Cádiz-Gurrea; Francesca Marongiu; Maria Cristina Meloni; Matteo Aroffu; Matteo Perra; Mohamad Allaw; Rita Abi Rached; Rodrigo Oliver-Simancas; et al. (Antioxidants, 2023)
Grape pomace is the main by-product generated during the winemaking process; since it is still rich in bioactive molecules, especially phenolic compounds with high antioxidant power, its transformation in beneficial and health-promoting foods is an innovative challenge to extend the grape life cycle. Hence, in this work, the phytochemicals still contained in the grape pomace were recovered by an enhanced ultrasound assisted extraction. The extract was incorporated in liposomes prepared with soy lecithin and in nutriosomes obtained combining soy lecithin and Nutriose FM06®, which were further enriched with gelatin (gelatin-liposomes and gelatin-nutriosomes) to increase the samples’ stability in modulated pH values, as they were designed for yogurt fortification. The vesicles were sized ~100 nm, homogeneously dispersed (polydispersity index < 0.2) and maintained their characteristics when dispersed in fluids at different pH values (6.75, 1.20 and 7.00), simulating salivary, gastric and intestinal environments. The extract loaded vesicles were biocompatible and effectively protected Caco-2 cells against oxidative stress caused by hydrogen peroxide, to a better extent than the free extract in dispersion. The structural integrity of gelatin-nutriosomes, after dilution with milk whey was confirmed, and the addition of vesicles to the yogurt did not modify its appearance. The results pointed out the promising suitability of vesicles loading the phytocomplex obtained from the grape by-product to enrich the yogurt, offering a new and easy strategy for healthy and nutritional food development.